Associations between lifetime classic psychedelic use and markers of physical health. (April 2021) - Simonsson, Otto; Sexton, James D; Hendricks, Peter S
Background: In recent years, there has been significant research on the mental health effects of classic psychedelic use, but there is very little evidence on how classic psychedelics might influence physical health. Aims: The purpose of the present study was to investigate the associations between lifetime classic psychedelic use and markers of physical health. Methods: Using data from the National Survey on Drug Use and Health (2015-2018) with 171, 766 (unweighted) adults aged 18 or above in the United States, the current study examined the associations between lifetime classic psychedelic use and three markers of physical health (self-reported overall health, body mass index, and heart condition and/or cancer in the past 12 months) while controlling for a range of covariates. Results: Respondents who reported having tried a classic psychedelic at least once in their lifetime had significantly higher odds of greater self-reported overall health and significantly lower odds of being overweight or obese versus having a normal weight. The association between lifetime classic psychedelic use and having a heart condition and/or cancer in the past 12 months approached conventional levels of significance, with lower odds of having a heart condition and/or cancer in the past 12 months for respondents who had tried a classic psychedelic at least once. Conclusion: The results of the present study suggest that classic psychedelics may be beneficial to physical health. Future research should investigate the causal effects of classic psychedelics on physical health and evaluate possible mechanisms.